Detection of asymptomatic lesions in jaws from patient visiting King Saud University (KSU) College of Dentistry: A retrospective study - Naveed Ahmad Khawaja; Mohammad Al Ali; Ahmad Bu Mozah; Hussain Al Marhoon (International Journal of Applied and Experimental Biology)
The aim of this study was to evaluate the detection of asymptomatic lesions of jaws in retrospective two-year panoramic radiographs from patients’ record visiting for treatment in the College of Dentistry, King Saud University, and accidentally noticed while patients visited for other reasons. Ninety-two (92) cases were selected for the study to detect asymptomatic lesions among 907 patients varying in age of 18 to 72 years (mean 38 years) and who visited the Dentistry College. The information was collected on a designed proforma by two examiners and calculated average. Seventy-six (76) were male and sixteen (16) females, including 79 (85.9%) radiopaque, 11 (12%) radiolucent, and 2 (2.2%) with mixed lesions. These results showed no significant gender differences. The selected cases were divided into three age groups 18-30, 31-50, and 51-72 years to detect different lesions, but the groups did not differ significantly. In this study, location-wise frequency of lesions in the anterior region of jaws were 2 (28.6%) in maxilla and 5 (71.4%) in mandible, whereas in the posterior region 7 (9.7%) were in maxilla and 65 (90.3%) in mandible. However, the study concluded that most of asymptomatic radiopaque lesions were found in the posterior region of mandible and more incidence being in young age group.